2004
DOI: 10.1007/s00228-004-0815-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cytochrome P450 isoforms involved in the metabolism of loperamide in human liver microsomes

Abstract: CYP2B6, CYP2C8, CYP2D6, and CYP3A4 catalyze LOP N-demethylation in human liver microsomes, and among them, CYP2C8 and CYP3A4 may play a crucial role in LOP metabolism at the therapeutic concentrations of LOP. Coadministration of these P450 inhibitors may cause drug interactions with LOP. However, the clinical significance of potential interaction of LOP metabolism by CYP2C8 and CYP3A4 inhibitors should be studied further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 28 publications
4
53
1
1
Order By: Relevance
“…It plays an important role in the metabolism of endogenous substances, e.g., arachidonic acid (Rifkind et al, 1995;Ohyama et al, 2000), as well as many drugs, including repaglinide (Bidstrup et al, 2003;Kajosaari et al, 2005a), pioglitazone (Jaakkola et al, 2006), rosiglitazone (Baldwin et al, 1999), loperamide (Kim et al, 2004), amiodarone (Ohyama et al, 2000), cerivastatin (Wang et al, 2002), and paclitaxel (Rahman et al, 1994). Thus, factors affecting CYP2C8 activity may have potentially important effects on drug efficacy and patient safety.…”
mentioning
confidence: 99%
“…It plays an important role in the metabolism of endogenous substances, e.g., arachidonic acid (Rifkind et al, 1995;Ohyama et al, 2000), as well as many drugs, including repaglinide (Bidstrup et al, 2003;Kajosaari et al, 2005a), pioglitazone (Jaakkola et al, 2006), rosiglitazone (Baldwin et al, 1999), loperamide (Kim et al, 2004), amiodarone (Ohyama et al, 2000), cerivastatin (Wang et al, 2002), and paclitaxel (Rahman et al, 1994). Thus, factors affecting CYP2C8 activity may have potentially important effects on drug efficacy and patient safety.…”
mentioning
confidence: 99%
“…Loperamide undergoes significant first pass metabolism by cytochrome CYP3A4 [7]. High concomitant doses of famotidine may inhibit CYP3A4 (this effect has been demonstrated for other histamine-2 receptor antagonistsparticularly cimetidine) [8][9][10].…”
Section: Discussionmentioning
confidence: 93%
“…A previous study reported that loperamide is metabolized to N-demethylated loperamide mainly by CYP3A4 in human liver microsomes 23) and that the metabolism is affected by CYP3A inhibition. 24,25) In contrast, because it is not clear whether loperamide inhibits CYP3A enzyme, our study was designed to focus on loperamide as a CYP3A inhibitor.…”
Section: Discussionmentioning
confidence: 98%